2021
DOI: 10.1002/ptr.7193
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of subgingivally delivered propolis as an adjuvant to nonsurgical periodontal treatment of periodontitis: A systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis evaluated randomized and nonrandomized studies that assessed the effect of local subgingival propolis as an adjunct to nonsurgical periodontal therapy (NSPT) in the treatment of periodontitis. A detailed search was carried out in Cochrane Library, Embase, LILACS, LIVIVO, PubMed, Scopus, and Web of Science, with no time or language restrictions. A grey literature search was also conducted. The methodology of included studies was evaluated by the Cochrane RoB2 tool. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…50 Previous systematic reviews concluded that treating periodontitis with propolis is safe and combined with conventional therapy may enhance the clinical parameters compared with non-surgical treatment alone or with placebo. 51,52 Assunção et al 51 excluded studies comprising patients with systemic disease. This reduces the power of propolis analysis in patients' systemic health.…”
Section: Discussionmentioning
confidence: 99%
“…50 Previous systematic reviews concluded that treating periodontitis with propolis is safe and combined with conventional therapy may enhance the clinical parameters compared with non-surgical treatment alone or with placebo. 51,52 Assunção et al 51 excluded studies comprising patients with systemic disease. This reduces the power of propolis analysis in patients' systemic health.…”
Section: Discussionmentioning
confidence: 99%